The Movement disorder associated with NMDAR antibody-encephalitis is complex and characteristic: an expert video-rating study - Varley, James A.; Webb, Alastair J. S.; Balint, Bettina; Fung, Victor S. C.; Sethi, Kapil D.; Tijssen, Marina A. J.; Lynch, Timothy; Mohammad, Shakeeb S.; Britton, Fiona; Evans, Matthew; Hacohen, Yael; Lin, Jean-Pierre; et al. (BMJ Journals, 2019)
N-methyl-D-aspartate receptor antibody-mediated encephalitis (NMDAR-AbE) is an increasingly recognised and treatable encephalitis, with a predilection for children and young adults.1 2 As earlier immunotherapy improves outcomes, timely and accurate recognition of NMDAR-AbE is a major clinical aim.2 - - The characteristic polysymptomatic presentation of NMDAR-AbE includes early neuropsychiatric deficits with seizures, autonomic disturbance, reduced consciousness and a movement disorder (MD).1 2 This MD, seen in around 90% of cases, can be the presenting feature, particularly in children,1 and is typically hyperkinetic with limb plus orofacial involvement.1-5 To date, elegant detailed descriptions exist in a few patients.4 However, small series have used highly variable phenomenological descriptions.1-5 Therefore, the phenomenology of the associated MD lacks consensus. Its clearer description will facilitate confident recognition and enable earlier immunotherapy administration in NMDAR-AbE. - - Expert-rater descriptions remain the gold standard to define phenotypes in movement disorders. In this study, ratings from seven experts across 76 videos were used to better define the MD in NMDAR-AbE. - - ### Subjects - - Autoimmune neurology researchers contributed 44 videos from 20 patients who met diagnostic criteria for NMDAR-AbE.e1 A PubMed search for ‘anti-NMDAR encephalitis’ and ‘NMDAR-antibody encephalitis’, plus associated references, revealed 32 videos from 14 subjects, in eight papers from 14 subjects.3 , e2-8 Clinical features, temporal progression, outcomes and investigation findings were collated from case note reviews by the researchers and from data in published papers. Twenty videos from 18 age-matched and sex-matched (age range 2-41 years, median 12, 50% female) disease controls were selected from the literature (online supplementary data).3 e9-19 - - ### Supplementary data - - [jnnp-2018-318584supp004.pdf] - - ### Movement disorder classification - - Seven experts (KB, VF, AEL, TL, NN, KS and MT) established a consensus glossary of terms (online supplementary data, modified from Mohammed et al 3). Subsequently, each expert blindly and independently rated 76 videos from 34 patients with NMDAR-AbE (median two videos …
Published: 21 July 2018
Gesehen am 27.09.2019